2018
DOI: 10.1186/s12888-018-1827-3
|View full text |Cite
|
Sign up to set email alerts
|

Hyperprolactinemia and insulin resistance in drug naive patients with early onset first episode psychosis

Abstract: BackgroundHyperprolactinemia and glucose and lipid metabolism abnormalities are often found in patients with schizophrenia and are generally considered secondary to the use of antipsychotic drugs. More recent studies have shown these same neuroendocrine and metabolic abnormalities in antipsychotic naïve patients with first episode psychosis (FEP), rising the hypothesis that schizophrenia itself may be related to an abnormal regulation of prolactin secretion and to impaired glucose tolerance. The aim of this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 49 publications
1
14
0
Order By: Relevance
“…Accumulating evidence indicates that subthreshold metabolic dysregulation might be present in the premorbid phase of the illness (59) and in antipsychotic-naïve patients with firstepisode psychosis (60), which has been confirmed in our report. We did not find hypercholesterolemia but hypertriglyceridemia in FEDN patients.…”
Section: Discussionsupporting
confidence: 88%
“…Accumulating evidence indicates that subthreshold metabolic dysregulation might be present in the premorbid phase of the illness (59) and in antipsychotic-naïve patients with firstepisode psychosis (60), which has been confirmed in our report. We did not find hypercholesterolemia but hypertriglyceridemia in FEDN patients.…”
Section: Discussionsupporting
confidence: 88%
“…Moreover, it has been shown that measuring the levels of fatty acids in subjects at ultrahigh risk of psychosis may improve prediction of transition to overt psychotic episode (41). Another study demonstrated that FEP patients have significantly higher levels of prolactin, fasting glucose, glycosylated hemoglobin and insulin resistance compared to individuals at clinical high risk of psychosis (42). It cannot also be excluded that results of our study simply reflect the effects of environmental factors or unhealthy lifestyle characteristics that are highly prevalent in early psychosis and include nutritional deficiencies as well as low exercise activity (43)(44)(45).…”
Section: Discussionmentioning
confidence: 99%
“…In the field of psychiatry, the adverse effects of Prl remain under debate. Treatment with psychiatric drugs to manage schizophrenia and depression is frequently associated with hyperprolactinemia (HPL), suggesting the negative effects of Prl in these patients 58,59 . In contrast, in a recent study, it was shown that many patients with a first episode of psychosis presented HPL before treatment and presented elevated rates of HPL over the course of the illness 60 .…”
Section: Discussionmentioning
confidence: 99%